Parametric Optimization of Surface Textures in Oil-Lubricated Long-Life Aircraft Valves - Pei Li; Qingxiang Pei; Zhe Liu; Sihai Luo; Liucheng Zhou; Junning Li; Leilei Chen (Lubricants)
The oil-lubricated long-life aircraft valve is one of the most important components to ensure the safety of the entire aircraft system, and it needs to operate millions of times during the whole service life, significantly necessitating techniques to enhance its tribological performance. To this end, five different surface textures, i.e., spherical cap, ellipsoidal cap, tree-frog, grass-lip and nepenthes textures were introduced to the pin’s surface of an aircraft valve to improve the valve’s tribological performance. By numerically solving the Reynolds equation with the Jakobsson–Floberg–Olsson cavitation boundary conditions, the effect of the five textures on the tribological performance was simulated. To optimize the geometric parameters of the five textures for a better tribological performance, the Analytic Hierarchy Process was introduced to derive a coupled tribological parameter, which accounts for three classical tribological parameters, including load bearing capacity, friction and friction coefficient. The five textures with optimal values of geometric parameters were also compared to one another using the Analytic Hierarchy Process, and this finally led to a suggestion of the best surface texture for the aircraft valve. The parametric optimization approach proposed in this work can be widely applied for the parametric optimization of surface textures in other applications.